2022
DOI: 10.3390/biom12020245
|View full text |Cite
|
Sign up to set email alerts
|

Differences According to Age in the Diagnostic Performance of Cardiac Biomarkers to Predict Frailty in Patients with Acute Heart Failure

Abstract: Frailty has traditionally been studied in the elderly population but scarcely in younger individuals. The objective of the present study is to analyze differences according to age in the diagnostic performance of cardiac biomarkers to predict frailty in patients admitted to the hospital for acute heart failure (AHF). A frailty assessment was performed with the SPPB and FRAIL scales (score > 3). We included 201 patients who were divided according to age: those older and younger than 75 years. In the younger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 34 publications
(34 reference statements)
1
10
0
Order By: Relevance
“…Finally, there are indications that certain biomarkers (such as NT-proBNP) may be associated with the presence of frailty in older HF patients. To further optimize frailty diagnosis, it may thus be promising to explore the potential role of biomarkers in future research [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, there are indications that certain biomarkers (such as NT-proBNP) may be associated with the presence of frailty in older HF patients. To further optimize frailty diagnosis, it may thus be promising to explore the potential role of biomarkers in future research [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…[34][35][36] In this sense, in young patients, frailty seems to be more determined by age and comorbidities; however, in the elderly, the HF severity represented by myocardial and remodelling stress marked by NT-proBNP has an impact on frailty. 37 In certain studies, it has been observed that frail patients have less often guideline-recommended medical treatment at discharge and follow-up, 38 although they obtained the most significant benefit. 39 Our data show similar neurohormonal treatment prescriptions at discharge between frail and non-frail patients but lower prescriptions in dependent patients than in independent ones.…”
Section: Discussionmentioning
confidence: 99%
“…25,40,41 One possible explanation is the relation between geriatric syndromes and cardiac damage reflected by an increase in cardiac biomarkers in frail and dependent patients. 37 Another possible underlying mechanism is the worse prognosis usually associated with comorbidities that are also more frequent in frail and dependent patients. 20 Similar to us, Sze et al studied the prognostic effect of frailty in AHF patients.…”
Section: Discussionmentioning
confidence: 99%
“…Ain et al [ 4 ] described the influence of several conditions such as age, sex, socio-economic status, body mass index, medication and other substance use, and medical illness, as well as inconsistencies in methodological practices such as sample collection, assaying, and data cleaning and transformation when dealing with the reproducibility of biomarkers in CVD. Aguilar-Iglesias et al [ 5 ] evaluated the impact of frailty and age on the performance of biomarkers in the diagnosis of acute heart failure (AHF). Frailty effectively impacts the performance of NT-proBNP in detecting AHF in patients older than 75 years old, while no influence was in younger [ 5 ].…”
mentioning
confidence: 99%
“…Aguilar-Iglesias et al [ 5 ] evaluated the impact of frailty and age on the performance of biomarkers in the diagnosis of acute heart failure (AHF). Frailty effectively impacts the performance of NT-proBNP in detecting AHF in patients older than 75 years old, while no influence was in younger [ 5 ]. Indeed, AHF might be considered a complex pathological entity derived from several conditions.…”
mentioning
confidence: 99%